The Emerald handbook of entrepreneurship in Latin America : unleashing a millennial potential - Montiel Méndez, Oscar Javier; Alvarado, Araceli Almaraz (Emerald Publishing Limited, 2022)
With contributions from nearly 50 researchers across Latin America, The Emerald Handbook of Entrepreneurship in Latin America: Unleashing a millennial potential contains the most important debates on creativity, innovation, and entrepreneurship in Latin America. Covering the most recent topics that influence Latin America's entrepreneurial dynamics, chapters are written by specialists from Mexico, Brazil, Canada, Chile, Colombia, England, Venezuela, Spain & Peru. The Emerald Handbook of Entrepreneurship in Latin America presents a detailed and extensive review of the most relevant literature published in Latin America, critically analysing and exposing historical processes along with emerging debates, suggesting future paths for its entrepreneurship ecosystems, agents, sectors and regions. The Emerald Handbook of Entrepreneurship in Latin America offers new perspectives and will change the way the global arena sees Latin America. A first must-have reference for present and future researchers, corporate executives, and business schools with the aim to understand the challenges and opportunities this region has in the global, national, and regional arenas, a timely text most relevant than ever given the post pandemic context that present and future generations will confront with.